Responsabilização por graves violações de direitos humanos na ditadura de1964-1985: a necessária superação da decisão do Supremo Tribunal Federal naADPF n° 153/DF pelo Direito Internacional dos Direitos Humanos - Emilio Peluso Neder Meyer (2012)
This research has as its object the colliding ways by which the highest institution of the Brazilian judiciary, the Supremo Tribunal Federal, and the jurisdictional institution of the inter-American system of human rights, the Inter-American Court of Human Rights, comprehend the Brazilian Amnesty Law of 1979, Act n° 6.683/1979. Specifically, the Part Idedicates to deconstruct the decision of the Supremo Tribunal Federal in the Arguição de Descumprimento de Preceito Fundamental n° 153/DF, analyzing the main opinions of the Justices and pinpointing the contradictions and mistakes made by them regarding the historical comprehension of the amnesty, the constitutional project opened by the Brazilian Constitution of 1988 and the International Law of Human Rights.On the other side, in Part II, it is analyzed the decision of the Inter-American Court of Human Rights in the Gomes Lund Case, by which it was determined the condemnation of the Brazilian State for the state omissions before the crimes of enforced disappearance occurredduring the Araguaia Guerrilla. Reflections about transitional justice and the implement or not of its elements in Brazil in the period after the Constitution of 1988 are also made. Herewith, the foundations for the confirmation of the hypothesis are available, concluding that the decision of the Inter-American Court of Human Rights must prevail in the prejudice of the decision of the Supremo Tribunal Federal, fixing as a part of the constitutional project of 1988, under the sign of a constitutional patriotism, the effectiveness of the transitional element of investigation and criminal accountability of agents that practiced the crimes of enforced disappearance in the context of the Araguaia Guerrilla and, also, any other perpetrators of serious violations of human rights during the dictatorship of 1964-1985.